2022
DOI: 10.1093/ecco-jcc/jjac037
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Work Presenteeism, and Exercise in Inflammatory Bowel Disease

Abstract: Background Chronic diseases, such as IBD, can lead to anxiety and depression which can have a significant impact on productivity at work (presenteeism). The aim of this study was to assess the prevalence of depression/anxiety, presenteeism and exercise levels amongst IBD patients. Methods This was a multicentre study whereby adult IBD patients, in clinical remission, were asked to answer an anonymous questionnaire. Hospital A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
1
18
2
Order By: Relevance
“…However, we also observed geographical differences. Specifically, patients from the northern region, western region, inland area, and economically underdeveloped area exhibited more severe psychological symptoms, which might be related to the social and cultural environment, lifestyle, economic status, medical resources, and psychological support and social networks available to patients in different regions 21–24 . For instance, a previous study has shown that the lifestyle of patients with IBD can significantly influence the occurrence of depression, 21 and patients in economically underdeveloped regions may face greater stress and lack of social support, leading to an increase in psychological symptoms 23 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, we also observed geographical differences. Specifically, patients from the northern region, western region, inland area, and economically underdeveloped area exhibited more severe psychological symptoms, which might be related to the social and cultural environment, lifestyle, economic status, medical resources, and psychological support and social networks available to patients in different regions 21–24 . For instance, a previous study has shown that the lifestyle of patients with IBD can significantly influence the occurrence of depression, 21 and patients in economically underdeveloped regions may face greater stress and lack of social support, leading to an increase in psychological symptoms 23 .…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, patients from the northern region, western region, inland area, and economically underdeveloped area exhibited more severe psychological symptoms, which might be related to the social and cultural environment, lifestyle, economic status, medical resources, and psychological support and social networks available to patients in different regions. [21][22][23][24] For instance, a previous study has shown that the lifestyle of patients with IBD can significantly influence the occurrence of depression, 21 and patients in economically underdeveloped regions may face greater stress and lack of social support, leading to an increase in psychological symptoms. 23 These findings emphasize the importance of incorporating psychological management into the routine treatment of IBD and considering geographical factors when developing personalized psychological intervention strategies, 25,26 as the occurrence of psychological abnormality itself varies by region.…”
Section: Discussionmentioning
confidence: 99%
“…However, in adults with type 2 diabetes, accelerometer-measured sedentary time was associated with increased levels of CRP in women but not men (β = 0.24, p = 0.04, β = 0.05, p = 0.54, respectively) [17]. Most studies completed in patients with IBD use self-report assessments of physical activity [18][19][20][21]. Self-report measures are more likely to be biased due to recall bias and measurement error.…”
Section: Introductionmentioning
confidence: 99%
“…CC varies from UC in location, in that it is segmental and causes inflammation impacting the whole digestive system from the mouth to the anus and can further cause inflammation deeper within all the intestinal layers (transmural and skip lesions) that may affect other organs through fistulation [ 3 , 4 ]. IBD has significant impacts on patient health quality of life (QoL), mental health, work productivity, and healthcare resources [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the US alone, the estimated annual direct treatment costs are greater than USD 6.8 billion, and indirect costs amount to an additional USD 5.5 billion [ 32 , 33 ]. The healthcare systems, both at the level of primary care and referral hospitals in developing nations, face significant infrastructural limitations as they lack the regular clinical supervision and laboratory assessments needed for evaluating, diagnosing, treating, and monitoring IBD patients [ 5 , 6 ], and will increasingly have difficulty affording the surgical treatment need of these patients as per the herewith presented approval guidelines compared to developed wealthy societies.…”
Section: Introductionmentioning
confidence: 99%